1999
DOI: 10.1177/000456329903600312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Erythropoietin Kits

Abstract: SUMMARY. Six erythropoietin (EPa) measurement kits from different manufacturers were evaluated for ease of use and performance. Reference values were compared from patient samples with normal and abnormal circulating serum EPa. The kits evaluated were EPO-Trac RIA, EPORIA, DSL RIA, EPa EIA, IBL ELISA and Medac ELISA (see below for manufacturers' details).The radioimmunoassay (RIA) methods were simple to perform with little preliminary preparation of reagents but the non-isotopic methods were of varying degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
2
10
1
1
Order By: Relevance
“…The precision and accuracy obtained in the present study were similar or better than those obtained in previous studies using the same [8,9,19] or other commercially available kits for EPO measurement [16,18]. Besides, estimated LOD and LOQ for CHEM and ELISA tests were lower than most of the previously reported methods [16][17][18].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The precision and accuracy obtained in the present study were similar or better than those obtained in previous studies using the same [8,9,19] or other commercially available kits for EPO measurement [16,18]. Besides, estimated LOD and LOQ for CHEM and ELISA tests were lower than most of the previously reported methods [16][17][18].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, EPO measurement has important clinical applications in differential diagnosis of anemia and polycythemia, and monitoring rhEPO administration in EPO deficient patients [18]. Usually, concentration of EPO in serum samples is measured by using immunological techniques [16][17][18][19]. The measurement methods need intralaboratory validation to assure satisfactory intra-and inter-assay precision and accuracy allowing clinically and analytically acceptable results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that there was a wide variation in results and the only assay that gave comparable results to the calibrator values was the assay that used 87/684 as a reference standard. 30 …”
Section: Measurement Of Epomentioning
confidence: 99%